2021
DOI: 10.1038/s41419-021-03734-4
|View full text |Cite
|
Sign up to set email alerts
|

TRIM25 regulates oxaliplatin resistance in colorectal cancer by promoting EZH2 stability

Abstract: Resistance to chemotherapy remains the major cause of treatment failure in patients with colorectal cancer (CRC). Here, we identified TRIM25 as an epigenetic regulator of oxaliplatin (OXA) resistance in CRC. The level of TRIM25 in OXA-resistant patients who experienced recurrence during the follow-up period was significantly higher than in those who had no recurrence. Patients with high expression of TRIM25 had a significantly higher recurrence rate and worse disease-free survival than those with low TRIM25 ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…For example, by regulating mitotic checkpoints and chromosome stability, TIF1 γ inhibits tumor progression [ 38 ]. Recently, epigenetic regulation was shown to play a vital role in the occurrence and development of tumors, such as regulating tumor resistance, proliferation, metastasis, and epithelial-mesenchymal transition [ 39 44 ]. Interestingly, prognostic model based on epigenetic regulation was constructed to predict patient prognosis, such as a prognostic model based on nine ferroptosis-related genes ( ALOX15 , CISD1 , CS , GCLC , GPX4 , SLC7A11 , EMC2 , G6PD , and ACSF2 ) that could predict the prognosis of breast cancer [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, by regulating mitotic checkpoints and chromosome stability, TIF1 γ inhibits tumor progression [ 38 ]. Recently, epigenetic regulation was shown to play a vital role in the occurrence and development of tumors, such as regulating tumor resistance, proliferation, metastasis, and epithelial-mesenchymal transition [ 39 44 ]. Interestingly, prognostic model based on epigenetic regulation was constructed to predict patient prognosis, such as a prognostic model based on nine ferroptosis-related genes ( ALOX15 , CISD1 , CS , GCLC , GPX4 , SLC7A11 , EMC2 , G6PD , and ACSF2 ) that could predict the prognosis of breast cancer [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…TRIM25, as a member of the E3 ubiquitination ligase family, has been reported to regulate the ubiquitination of various proteins. 37 Here, we showed that GADD45A might recruit TRIM25 and increase the total ubiquitination and degradation of ATP5A1. The biochemical link between GADD45A and ATP5A1 appears to be a critical pathogenic mechanism during the development of adipogenesis and skeletal muscle metabolic diseases.…”
Section: Discussionmentioning
confidence: 72%
“…Similarly, in bladder cancer cells, overexpressed RITA1 induced degradation of RBPJ by recruiting the E3 ligase TRIM25 [ 80 ]. In this case, however, RBPJ proteolysis appeared to increase malignancy, which may apply for other cancer types linked to TRIM25 activity as well [ 80 , 81 , 82 , 83 ].…”
Section: Discussionmentioning
confidence: 76%